Sudden death of a child associated with invasive non-typeable Haemophilus influenzae infection with underlying IgG2 subclass deficiency. (May 2023) - Abe, Yuriko; Takano, Chika; Tie, Jian; Isobe, Eiji; Ohirabaru, Ayumi; Isahai, Isamu; Nishiyama, Hiroyuki; Jike, Toyoharu; Masuda, Shinobu; Okuda, Takahisa
Highlights: Haemophilus influenzae can be of either typeable or non-typeable strains. Infections caused by non-typeable Haemophilus influenzae are less likely to be fatal. Recently, there has been an increase in reports of invasive non-typeable Haemophilus influenzae infections, which cause meningitis, sepsis, or acute pneumonia. For immunocompromised children, invasive non-typeable Haemophilus influenzae infection can result in sudden death. Abstract: Haemophilus influenzae can be divided into typeable and non-typeable strains. Although non-typeable Haemophilus influenzae (NTHi) is less likely to be a fatal bacterium, invasive NTHi infection has been reported to increase worldwide. This study presents a case of sudden death of a child with invasive NTHi infection and underlying immunoglobulin G2 (IgG2 ) deficiency. A two years seven months male child with a high fever was found unresponsive in bed, lying face down on a soft pillow. Later, the hospital declared the subject dead. An autopsy revealed that the only noteworthy finding was tissue congestion. The histopathological findings disclosed neutrophils within blood vessels of major organs. Meanwhile, the formation of the micro abscess was not visible, which indicated bacteremia. The bacterial blood culture was positive for Haemophilus Influenzae . Polymerase chain reaction assay revealed the absence of an entire capsule locus. The transmission electron microscopy showed that the colonies did not have polysaccharide capsules. Based on the above findings, the strain was identified as NTHi. Furthermore, the value of serum IgG2 was deficient, indicating the presence of IgG2 subclass deficiency. The subject eventually died from asphyxia by smothering due to a comorbid condition with a high fever brought on by NTHi-induced bacteremia and lying face down. IgG2 subclass deficiency contributed to the development of invasive NTHi infection. The invasive NTHi infection might present a risk of sudden death, particularly for immunocompromised children. As forensic pathologists and pediatricians may encounter such a problematic clinical condition, they should be aware of this.